Lipoprotein Profile Modifications during Gestation: A Current Approach to Cardiovascular risk surrogate markers and Maternal-fetal Unit Complications - Ana Paula Caires dos Santos; Ricardo David Couto (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2018)
Abstract Several changes occur in lipid metabolism during gestation due to hormonal and metabolic changes, which are essential to satisfy the nutritional demands of the maternal-fetal unit development. The gestation shows two distinct periods that begin with fat accumulation, mainly in maternal adipose tissue, and the late phase, characterized by accelerated catabolism, with the increase of fatty acids in the circulation that causes hyperlipidemia, especially the one characterized as hypertriglyceridemia. Maternal hyperlipidemia may be associated with the development of maternal-fetal complications (preterm birth, preeclampsia, vascular complications) and the development of long-term cardiovascular disease. The cardiovascular risk may not only be related to lipoproteins cholesterol content, but also to the number and functionality of circulating lipoprotein particles. This review reports themajor changes that occur in lipoprotein metabolismduring pregnancy and that are associated with the development of dyslipidemias, lipoprotein atherogenic phenotype, and maternal-fetal unit complications.